How connected are the major forms of irrationality? An analysis of pseudoscience, science denial, fact resistance and alternative facts - Sven Ove Hansson (Mètode Science Studies Journal: Annual Review)
Science is a fact-finding practice, but there are many other fact-finding practices that apply largely the same patterns of reasoning in order to achieve as reliable information as possible in empirical issues. The fact-finding practices form in their turn a subcategory of rational discourse, a wider category that also encompasses argumentation on non-empirical issues. Based on these categories, it is easy to see the relationship between on the one hand pseudoscience, and on the other hand fact resistance, disinformation, and fallacies of reasoning. The flaws in argumentation are similar, and the main difference is whether or not the subject matter falls within or without the realm of science.